Automated processes in tennis: Do left-handed players benefit from the tactical preferences of their opponents? - Loffing, F.; Hagemann, N.; Strauss, B. (Journal of Sports Sciences, 2010)
Previous research on laterality in sport suggests an over-representation of left-handers in interactive sports such as tennis and cricket. These findings potentially reflect left-handers' advantage over their right-handed competitors in those sports. Although considered crucial for successful performance, the tactical component of their superiority has yet to be analysed. Two studies were conducted to test for a side bias in tennis players' tactical preferences. In the first study, 108 right- and left-handed players of varying skill watched rallies on a computer screen and had to indicate where they would place the ball in the opposing half. The results showed the tactical preference of players to place more balls on a left-handed opponent's mostly stronger forehand side compared with when faced with a right-hander. In the second study, 54 professional tennis matches involving right- and left-handers were analysed with respect to ball placement frequencies on the opponent's backhand side. Significantly fewer balls were hit to the backhand side of a left-handed opponent, thus replicating the findings of Study 1 in on-court situations. Both studies indicate players' preference to place shots to their right irrespective of their opponent's handedness. Findings support the assumption that left-handers might enjoy a strategic advantage in tennis.